Risco biológico nas etapas finais do sistema de medicação em serviços de urgência e emergência e a implementação de uma estratégica educativa pautada no Arco de Maguerez - Mendonça, Katiane Martins (2013)
INTRODUCTION: the prepare and the administration medications´s are activities performed by nursing staff and involve the biological risk to users and to professionals. This risk may be exacerbated when work activities are developed in areas such as emergency care that require immediate decisions. For intervention in this reality is necessary be based on situational analysis and involve all staff in the change process. OBJECTIVES: the general was to analyze the biological risk in the final stages of the medication system in the context of emergency services. And the specifics were to identify the recognition by nursing staff on the occurrence of behaviors that are characterized as biological risk in the final stages of the medication system, in the context of emergency services; characterize cases of accidents with biological material during the administration of medication in emergency services; describe ways to reduce the occurrence of accidents, indicated by the victims during the administration of medications in emergency services and describe the process of implementing an educational intervention on the biological risk in the prepare and the administration medications´s based on Problematization Methodology with Maguerez´s Arch. METHOD: The study was divided into two stages. The first presented an analytical design. Data collection occurred from October/2011 to April/2012, using a questionnaire, with demographic data and related accidents with biological material and Likert scale, with 44 items about risk behaviors previously observed among the study participants. The instruments were subjected to pilot testing. The data were processed by SPSS / IBM 20.0. In the second stage there was a descriptive exploratory study with a qualitative approach. The sources of information were recordings of the group discussions, field notes and record the speeches in the posters. The data´s collection, analysis and presentation were guided by the stages of the Arch and the guidelines of Bogdan and Biklen (2010). The educational intervention was performed in 44 meetings 34 professionals, in small groups, from August to December 2012. All went through by the stages of Maguerez´s Arch (reality observation, problem definition, key points, theorizing, possible solutions and application to reality). The project was approved by the Ethics Committee number 065/08 and 118/08 and all participants signed the informed consent. RESULTS: The scale showed the recognition by professionals of the existence of conduct that characterized the biological risk. The scale showed satisfactory reliability (Cronbach's alpha of 0.75 overall) and showed the recognition by professionals of the existence of conduct that characterized the biological risk. The conducts were related to the practice of hand washing, protective equipment, maintenance of aseptic chain, waste of health services and occupational accidents. The accident rate was 41.7% and most of the victims worked at night and said it had not received training to work in the emergency department. The protection items were neglected. Individual and organizational issues were identified as ways to reduce accidents. The educational intervention in these departments required adaptations. Were held 44 meetings with the participation of 34 professionals (87.2% of the population), six nurses and 28 nursing technicians, divided into small groups, from August to December/2012. All went through the steps of the Maguerez´s Arch (observation of reality, problem definition, key points, theorizing, possible solutions and application to reality). From the proposal for discussion of the problem related to the practice of preparation and administration of medications in emergency care unit, the key points prioritized contemplated infrastructure, human and material resources and staff qualification. Theorizing complemented the stage of the search for possible solutions, among which could be implemented in the short, medium and long term. The evaluation of the implementation of this strategy showed the commitment of professionals with field experience and successful methodology. CONCLUSION: all accidents reflected the configuration of risk behaviors recognized. The essence of this study was to understand the practice where it gives, with our own eyes, the eyes of the other and together seek a path to transformation. We found that the route chosen for the study provided us subsidies to analyze and reflect on the process of intervening in questions about the biological risk units with the wealth of specifics, such as emergency departments and direct strategies for use in units with characteristics like.